SECURITY ASSESSMENT OF IEEE 802.16 (WIMAX) – A SHORT COMPARISON BETWEEN IEEE 802.16d AND 802.16e - Eren, Evren (International Journal of Computing, 2014)
The importance of IEEE-Standard 802.16 (WiMAX) is growing and will compete with technologies such as UMTS. However, acceptance and adoption of technologies and services also depend on security. Therefore, this article will deal with some of the basic security features of IEEE 802.16d (Fixed WiMAX). It will summarize the most important elements of the security architecture, present some of its weaknesses, potential attacks and viable counter measurements. Furthermore, we will introduce the basic improvements made by the IEEE 802.16e standard (Mobile WiMAX) compared to Fixed WiMAX. This article extends the paper [11] presented at the IDAACS'2007 conference by describing the data encryption mechanisms in IEEE 802.16e in chapter 4.